Molecular identification and transmission studies of X-cell parasites from Atlantic cod Gadus morhua (Gadiformes: Gadidae) and the northern black flounder Pseudopleuronectes obscurus (Pleuronectiformes: Pleuronectidae). - Freeman, M.A.; Eydal, M.; Yoshimizu, M.; Watanabe, K.; Shinn, A.P.; Miura, K.; Ogawa, K. (BMC, 2011)
The inability to successfully transmit both parasites in this study suggests that either host detachment combined with a period of independent development or an alternate host is required to complete the life cycle for X-cell parasites. Phylogenetic analyses of SSU rDNA confirm a monophyletic grouping for all sequenced X-cell parasites, but do not robustly support their placement within any established protist phylum. Analysis of SSU rDNA from X-cells in Japanese flatfish reveals that the same parasite can infect more than one species of fish.